Rancang Bangun Antena Yagi untuk Mengubah Pola Radiasi pada Radio Telemetri 433 MHz di Mortir Latih: Telekomunikasi Militer - Kurniawan Syaputra; Vincensius Arga Yoda; Imam Ashar (Jurnal Telkommil, 2024)
Abstract—Conventional radar systems use a mechanical system to direct the antenna beam during the search/scanning process. This research aims to design and analyze a Microstrip Patch Rectangular Array Antenna for directing antenna beams in Radar systems. The results of the analysis and design show that the Microstrip Planar Array Rectangular Patch antenna based on calculations using empirical formulas can operate at radar frequencies. Microstrip antennas can work on the Ultra Wide Band (UWB) line and work at a resonant frequency of 1.5 GHz with an antenna gain of 8.70 dB. The Voltage Standing Wave Ratio (VSWR) value is 1.43